Forecasting and regulation of costs for the construction of heating networks for public needs - Matsapura, О. (Ways to Improve Construction Efficiency, 2018)
It is expedient to determine the effectiveness of public procurement regulation in the field of construction in view of the added value created as a result of construction works. As you know, value added shows how much higher the cost of the final product compared to the means of production spent [1]. For construction, value added may be a sum of money calculated by subtracting from the result of the consolidated estimate the cost of building materials, products and structures.